Associations Between Gestational Weight Gain and Adverse Birth Outcomes: A Population-Based Retrospective Cohort Study of 9 Million Mother-Infant Pairs - Liu, Xue; Wang, Huan; Yang, Liu; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Nutrition, 2022)
Background Gestational weight gain (GWG) reflects maternal nutrition during pregnancy. However, the associations between maternal GWG and adverse birth outcomes are inconclusive. Objective We aimed to examine the associations between maternal GWG and adverse birth outcomes according to maternal pre-pregnancy body mass index (BMI) categories in a large, multiethnic and diverse population in the U.S. Study Design We used nationwide birth certificate data from the National Vital Statistics System to examine the association of GWG (below, within and above the Institute of Medicine [IOM] guidelines) with six adverse birth outcomes (preterm birth, low birthweight, macrosomia, small for gestational age [SGA], large for gestational age [LGA], and low Apgar score) according to the pre-pregnancy BMI categories (underweight to obesity grade 3). Multivariable logistic regression analyses were performed to estimate the odds ratios (ORs) and 95% confidence intervals (CIs). Results A total of 9,191,842 women aged 18–49 years at delivery with live singleton births were included. Among them, 24.5% of women had GWG below IOM guidelines, 27.6% within the guidelines, and 47.9% above the guidelines. Compared with maternal GWG within guidelines, GWG below guidelines was associated with higher odds of preterm birth (OR = 1.52, 95%CI = 1.51–1.53), low birthweight (OR = 1.46, 95%CI = 1.45–1.47) and SGA (OR = 1.44, 95%CI = 1.43–1.45). In contrast, maternal GWG above guidelines was associated with higher odds of macrosomia (OR = 2.12, 95%CI = 2.11–2.14) and LGA (OR = 2.12, 95%CI = 2.11–2.14). In addition, maternal GWG below or above guidelines had slightly higher odds of low Apgar score (below guidelines: OR = 1.04, 95%CI = 1.03–1.06, above guidelines: OR = 1.17, 95%CI = 1.15–1.18). The results were largely similar among women with GWG below or above guidelines across pre-pregnancy BMI categories of underweight, overweight, and obesity grade 1 to grade 3. Conclusion Pregnant women with GWG below or above the IOM guidelines have increased odds of selected adverse infant birth outcomes. Monitoring maternal GWG could enable physicians to provide tailored nutrition and exercise advice as well as prenatal care to pregnant women to reduce the likelihood of adverse birth outcomes.